Temperature and pressure dependence of Raman active lattice mode frequencies of cubic C8H6(Br)2, evidence of a phase transition. (1st February 2019) - Owens, Frank J.
ABSTRACT: The temperature dependence of the Raman active frequencies of the lattice modes of dibromocubane is measured below room temperature. The frequencies are linearly dependent on the temperature decreasing with increased temperature with a marked change in slope occurring at 200 K indicative of a structural phase transition. The pressure dependence of the frequencies measured at room temperature up to 24 KBar shows no evidence of a phase change. Density functional calculations of the structure and Raman frequencies of the internal modes of an isolated molecule of C8 H6 (Br)2 indicate the molecule is slightly distorted from a cubic carbon structure.